An analytical model to predict spalling and breaching of concrete plates under contact detonation - Tu, Huan (2022)
Under contact and close-in detonation, severe local failure is commonly observed on concrete elements and structures. So far prediction tools are available as empirically-based design diagrams, PC tools through replication scaling, or as physics based Finite Element Models (FEM). The last tool requires significant computational efforts and expertise from the modeler. As a fast and physics-based alternative, an analytical model is proposed in Tu et al.’s work [1], to quantitively predict compressive damage forming on the impacted face. In this paper, subsequent studies are conducted to (1) predict spalling damage size on the rear face and (2) predict whether concrete plates are breached by contact detonation. The analytical predictions are validated against a range of experimental data from published references. Good agreement shows the capability of the proposed model in effectively predicting local damage size and breaching of concrete plates subjected to contact detonation.